Cancer-associated venous thromboembolism: Burden, mechanisms, and management - Ay, Cihan; Pabinger, Ingrid; Cohen, Alexander T. (Thrombosis and Haemostasis, 2017)
Venous thromboembolism (VTE) is a significant health problem in the general population but especially in cancer patients. In this review, we discuss the epidemiology and burden of the disease, the pathophysiology of cancer-associated VTE, and the clinical treatment options for both primary prevention and acute treatment. Overall, the development of VTE in cancer patients is related to increases in morbidity, mortality, and medical costs. However, the incidence of cancer-associated VTE varies due to patient-related factors (e.g. thrombophilia, comorbidities, performance status, history of venous diseases), tumour-related factors (e.g. cancer site, stage, grade), and treatment-related factors (e.g. surgery, chemotherapy, anti-angiogenesis treatment, hormonal and supportive treatment). Furthermore, blood count parameters (e.g. platelets and leukocytes) and biomarkers (e.g. soluble P-selectin and D-dimer) are predictive markers for the risk of VTE in cancer patients and have been used to enhance risk stratification. Evidence suggests that cancer itself is associated with a state of hypercoagulability, driven in part by the release of procoagulant factors, such as tissue factor, from malignant tissue as well as by inflammation-driven activation of endothelial cells, platelets, and leukocytes. In general, low-molecular-weight heparin (LWMH) monotherapy is the standard of care for the management of cancer-associated VTE, as vitamin K antagonists are less effective in cancer patients. Direct oral anticoagulants (DOACs) offer a potentially promising treatment option for cancer patients with VTE, but recommendations concerning the routine use of DOACs should await head-to-head studies with LMWH.
Keywords: venous thromboembolism; cancer; epidemiology; risk factors; treatment